2020
DOI: 10.3390/civileng1020010
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-Activated Binders Based on Tungsten Mining Waste and Electric-Arc-Furnace Slag: Compressive Strength and Microstructure Properties

Abstract: The valorization and reusing of mining waste has been widely studied in recent years. Research has demonstrated that there is great potential for reusing mining waste for construction applications. This work experimentally investigated the strength development, pore structure, and microstructure of a binary alkali-activated binder. This is based on tungsten mining waste mud (TMWM) and electric-arc-furnace slag (EAF-Slag) using different proportions of TMWM (10, 20, 30, 40, and 50 vt.%). The precursors were act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…This is significant to the change in the matrix structure of the geopolymer bonds affected by the addition of GGBS and fly ash [ 45 , 46 ]. The altering peaks which shift the wavenumbers of Si–O–T asymmetric stretching and Si–O–T bending vibration, from 996.62 to 1013 cm −1 and 678.78 to 784 cm −1 of geopolymer soil samples indicated that the stabilization/solidification process of the geopolymer is a chemical reaction and the geopolymerization is active at room temperature [ 60 ]. This finding is in line with a previous study conducted by Sedira et al [ 60 ] that reported a shift in peaks to increase the wavenumbers of Si–O–T asymmetric stretching and Si–O–T bending vibration, clearly indicated that the alkali-activated could cause an increase in the compression strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is significant to the change in the matrix structure of the geopolymer bonds affected by the addition of GGBS and fly ash [ 45 , 46 ]. The altering peaks which shift the wavenumbers of Si–O–T asymmetric stretching and Si–O–T bending vibration, from 996.62 to 1013 cm −1 and 678.78 to 784 cm −1 of geopolymer soil samples indicated that the stabilization/solidification process of the geopolymer is a chemical reaction and the geopolymerization is active at room temperature [ 60 ]. This finding is in line with a previous study conducted by Sedira et al [ 60 ] that reported a shift in peaks to increase the wavenumbers of Si–O–T asymmetric stretching and Si–O–T bending vibration, clearly indicated that the alkali-activated could cause an increase in the compression strength.…”
Section: Resultsmentioning
confidence: 99%
“…The altering peaks which shift the wavenumbers of Si–O–T asymmetric stretching and Si–O–T bending vibration, from 996.62 to 1013 cm −1 and 678.78 to 784 cm −1 of geopolymer soil samples indicated that the stabilization/solidification process of the geopolymer is a chemical reaction and the geopolymerization is active at room temperature [ 60 ]. This finding is in line with a previous study conducted by Sedira et al [ 60 ] that reported a shift in peaks to increase the wavenumbers of Si–O–T asymmetric stretching and Si–O–T bending vibration, clearly indicated that the alkali-activated could cause an increase in the compression strength. This finding proves that the geopolymerization method effectively increases the mechanical and physical properties of the soil based on the increase in compressive strength of the geopolymer soil with GGBS and fly ash.…”
Section: Resultsmentioning
confidence: 99%
“…mortar, concrete), for binder and aggregate partial replacement in building materials. Alkali activated products [8] and pozzolanic materials [9] were successfully produced with tungsten mining residues. The durability of conventional products may be enhanced in terms of resistance to abrasion and acid attack due to a lower water absorption [10].…”
Section: Introductionmentioning
confidence: 99%